OP50 Disparities in Mortality and Deaths Amenable to Healthcare Intervention in Adults with Intellectual Disability. (13th September 2016) - Hosking, FJ; Carey, IM; Harris, T; De Wilde, S; Beighton, C; Cook, DG; Shah, SM
Abstract : Background: It is widely recognised that people with intellectual disability (ID) experience poorer health, access to healthcare and life expectancy. However there is limited accurate population-based information on their mortality, which is crucial to forming strategies to reduce premature deaths. We examined mortality in a large unselected group of adults with ID, with a focus on those deaths considered potentially avoidable. Potentially avoidable deaths are widely used as a means of assessing healthcare systems, as they are deaths which could have been avoided by good quality healthcare (sub-defined as amenable) or public health interventions (sub-defined as preventable). Methods: We described the mortality experience of adults with ID compared to the general population using novel linkage of two national databases, namely general practice data from the Clinical Practice Research Datalink (CPRD) and ONS mortality data. We used a matched cohort study from 343 English general practices between 2009 and 2013. 16, 666 adults with ID (656 deaths) aged 18–84 were compared to 113, 562 age, sex and practice matched controls (1, 358 deaths). Outcomes of all-cause and cause specific mortality as well as deaths considered potentially avoidable, were examined using stratified Cox regression in SAS. Results: Adults with ID had higher mortality rates than controls (Hazard Ratio (HR) = 3.6, 95% CI = 3.3–3.9) which remained high after adjusting for co-morbidities, smoking and deprivation (HR = 3.1, 2.7–3.4). The higher mortality rate compared to controls was greater among ID adults with Down's syndrome (HR = 9.2, 7.2–11.8) and epilepsy (HR = 6.0, 5.0–7.2). Almost all cause specific rates were higher for ID adults, with greatest increases (HR > 10) for genitourinary and nervous system diseases/disorders. While potentially avoidable deaths constituted similar percentages of overall mortality in both the ID group (46.3%) and controls (47.5%), the contribution from deaths classified as amenable was very different; 37.0% of all deaths in the ID group compared to 22.5% in the controls. This difference was reflected in the HR for deaths amenable to healthcare (HR = 5.1, 4.5–5.8) in contrast to the other subcategory of avoidable deaths (Preventable deaths HR = 1.7, 1.49–2.0). Conclusion: Mortality among adults with ID is markedly elevated compared to the general population. This disparity is particularly prominent in deaths which are considered potentially avoidable through good quality healthcare. This mortality disparity may be an indicator of healthcare inequality and effectiveness; therefore strategies are needed to improve access and quality of healthcare for people with ID.